Chocolate: Origins, current technology and production of antioxidants beneficial to health - Chévez-Vera, Héctor David (2021)
The current review entitled Chocolate: Origins, current technology and production of beneficial antioxidants for health, presents us with a compilation of researchs on the origin, history and benefits of chocolate as a superfood that contributes to the daily diet not only with empty carbohydrates; but also, with a number of complex chemical antioxidants compounds such as flavonoids, theobromine, caffeine among others, wich contribute to the health and development of the human being in all stages of their life, thus also improving the cognitive and immunological capacities of those who consume this product. All the aforementioned characteristics of this product of tropical origin require a deeper knowledge of each of its possible benefits and what are the effects on its consumption in the long and short term